Upskilling Desain Grafis Produk Percetakan Siswa SMK di Janapria Kabupaten Lombok Tengah - Pribadi, Agus; S, Suriyati; Rismayati, Ria (Yayasan Daarul Huda Kruengmane, 2024)
Vocational high school graduates in Central Lombok Regency tend to enter the workforce. Only a small number continue to higher education. In even smaller numbers, some try to open their own businesses or work independently. Based on findings in the field, vocational high school graduates in Central Lombok Regency are generally not ready to directly apply their skills and potential to enter the workforce. However, the choice of vocational high school is a choice of urgency and the desire to work quickly but in reality are not ready to go straight to work directly. This condition also applies especially to students and vocational high schools whose field of expertise is Multimedia sub-Graphics and Printing Products. The community service activity team provides a solution to partners by providing direct practical guidance/mentoring to students in order to increase the capacity of students' skills in making printing product designs. The method of implementing the activity consists of the stages of identification, planning, implementation, and evaluation. Based on the evaluation results, the capacity of students can increase. Students can make graphic designs for printing products that are tailored to the needs of the world of work and industry. Students gain additional experience in preparing themselves to enter the workforce after graduation.